A retrospective analysis of dexmedetomidine and morphine in the fast‐track and ultra‐fast‐track extubation protocol after congenital cardiac surgery. Issue 12 (26th July 2022) - Altun, Dilek; Arnaz, Ahmet; Doğan, Abdullah; Yalçinbaş, Yusuf; Türköz, Rıza; Oktay, Ayla; Yüksek, Adnan; Altun, Demet; Sarıoğlu, Tayyar
Abstract: Background and Aim of the Study: After congenital cardiac surgery, the duration of mechanical ventilation (MV) is related to the clinical status, type of operation, and the sedative‐analgesic agents used postoperatively. This study aims to examine the effects of dexmedetomidine and morphine on the fast‐track extubation (FTE) and ultra‐fast‐track extubation (UFTE) protocol after congenital cardiac surgery. Methods: A total of 251 pediatric patients were divided into two groups: 118 patients in the morphine group (Group M) and 133 patients in the dexmedetomidine group (Group D). We retrospectively reviewed medical data including hemodynamic parameters, duration of MV and cardiovascular intensive care unit (CICU), additional sedative/analgesic requirement, adverse events, the need for reintubation, and noninvasive MV, sedation, and pain scores. Results: The mean mechanical ventilation duration of Group D was significantly shorter than Group M (3.74 ± 0.83 h in Group D, 5.72 ± 1.54 h in Group M, respectively) ( p = .001; p < .05). In Group D, the success rate of FTE was 92.5% ( n = 123) and UFTE was 7.5% ( n = 10) ( p = .001). In Group M, the success rate of FTE was 72.9% ( n = 86) and UFTE was 0% ( n = 0) ( p > .05). Conclusions: Dexmedetomidine and morphine have clinical benefits which encourage their use for FTE protocol. Dexmedetomidine has more benefits compared to morphine. It can be used in UFTE protocol, besides its use in FTE protocol with fewer side effects.